Tight junctional protein family, Claudins in cancer and cancer metastasis - Wenxiao Ji; Xinguo Zhuang; Xinguo Zhuang; Wen G. Jiang; Tracey A. Martin (Frontiers in Oncology)
Claudin (CLDN) family proteins are key components of tight junctions in epithelial and endothelial cells, crucial for controlling paracellular permeability and cell-cell adhesion. Aberrant CLDNS expression is frequently observed in cancers and has been linked to tumor progression, invasion, and metastasis. Recent years have seen a rapid advance in exploring the role played by this protein family in cancer and cancer metastasis, and even chemotherapy response. This article provides a comprehensive overview of the roles of CLDNs in solid tumors, highlighting how specific CLDN members function as oncogenic drivers or tumor suppressors in different cancer types. We also discuss the potential of CLDNs as biomarkers for prognosis and therapeutic targets (e.g. CLDN18.2-targeted immunotherapy). The inclusion of updated literature (particularly post-2020) and bioinformatic analyses (TCGA/GEPIA) reveal emerging trends. Finally, we summarize common patterns of CLDN dysregulation across cancers and outline future research directions, including pan-cancer CLDN analyses and translational strategies.